Evaluation of the G-8 test as a screening for comprehensive geriatric assessment in older patients with cancer - Oscanoa, Teodoro J. (2024)
Objective: To evaluate sensitivity and specificity of the G8 test in screening older adults with cancer who may benefit from a Comprehensive Geriatric Assessment (CGA). Material and methods: This observational retrospective study was carried out in the Geriatrics Service of the Guillermo Almenara Hospital in Lima, Peru. CGA reports were reviewed in the electronic medical records of older adults (> 60 years) with cancer, both outpatients and inpatients, between November 2022 and July 2023. Patients were classified according to the SIOG-1 (International Society of Geriatric Oncology) criteria into two groups: fit and non-fit patients (vulnerable + frail + too sick). Sensitivity, specificity, and positive predictive value, area under the receiver operating characteristic curve (AUC), were estimated for the G8 test. Results: 201 patients entered the study, 91 women (45.3%) and 110 (54.7%) men; their mean age was 76.2 ± 7.4 years. The most frequent neoplasms were colorectal, stomach, prostate, and bile ducts. The prevalence of eligible and unfit patients was 23.4% and 76.6%, respectively. When the G8 test score was ≤11, sensitivity, specificity, positive predictive value, and AUC were 73.4% (95% Confidence Interval: 65.7- 80.2%), 91.5% (79.6%-97.6%), 96.6% (91.7-98.6%), and 89% (84-93%), respectively. Conclusions: The G8 test with a score ≤11 would have high sensitivity and specificity for identifying vulnerable or frail patients with cancer who could benefit from the CGA.